Public Policy Innovation as an Effort to Increase Community Participation in the Public Decision Making Process - Prasetyo, Hendrawan (Spirit Publik: Jurnal Administrasi Publik, 2024)
This research aims to determine community participation in the public decision-making process, to determine the obstacles faced by the society in participating in the public decision-making process, to analyze public policy innovations carried out by the Kebumen Regency Government which can increase community participation in the decision-making process the public, as well as to provide policy recommendations to the Kebumen Regency Government in increasing community participation in the public decision-making process and to understand community participation in the public decision-making process. This research uses a qualitative approach, namely trying to get as complete information as possible about how innovation works policy public can increase community participation in the retrieval decision process public in the District Kebumen. Community participation is very important in ensuring targeted and relevant policies that can address society needs. Participation also functions as a form of community representation and control over the policies implemented. Based on results study can is known that is one example of public policy innovation carried out Government Regency Kebumen are the "Lapor Bupati" (Reporting to the Regent) and "Mubeng Bumen" programs implemented by the Kebumen Regency government. This initiative has proven to be quite effective in increasing community participation. Ultimately, this research aims to provide valuable input for policy makers to formulate and implement public policies that can encourage greater community involvement, thereby realizing better governance. Keywords: community participation; community involvement; innovation; public policy